Aufforderungssatz in Recipes on the Chefkoch.de Website - Azizah Ayuning Tyas; Kurniasih Ratri Handayani; Uryadi Rohimin (Universitas Negeri Malang, 2026)
This qualitative study aims to identify the forms of directive sentences (Aufforderungssätze) in German-language cooking recipes on the website Chefkoch.de. Using a descriptive analysis method based on the theories of Helbig and Buscha (2001) and Engel (1993), data were collected from 12 selected recipes with the highest ratings (4.5–4.9/5), representing four dish categories. Analysis of 214 Aufforderungssätze showed that Infinitivkonstruktionen (142 sentences) were the most dominant form, followed by Aussagesätze im Präsens oder Futur (42 sentences), Imperativsätze (21 sentences), Einwortsätze (4 sentences), and Fragesätze (1 sentence). The findings also revealed the use of two forms not covered by the theoretical classification, namely Aussagesätze im Perfekt (2 sentences) and Aussagesätze im Passiv (2 sentence), while the forms of isolated subordinate clauses and the present subjunctive with the pronoun “man” were not found in the analyzed data.